2022
DOI: 10.21931/rb/2022.07.04.26
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid addition and spraying with ginger rhizome extract on the growth and some chemical contents of apricot seedlings Prunus armeniaca L . cv.

Abstract: This study was conducted at the slat house of the Department of Horticulture and Landscaping - College of Agriculture / Anbar University, during the growing season of 2021. The effect of soil application of humic acid (H) at 0, 4, 8 ml L-1 and ginger rhizome extract (Z) spraying at 0, 5, 10 g L-1 on some growth characteristics and some chemical contents of apricot seedlings, cultivar Hamawi was studied. Eighty-one two-year-old seedlings were selected that grafted on the stock of the apricot seed. A two-factor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

6
0

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…It has been observed that cracking of fruits is not by a single gene, but by several genes, and this trait can be inherited in plants (Vaidyanathan and Harrigan, 2005). The level of cracking differs significantly among several varieties [31][32][33]. In a study on seedless pomegranate varieties, it was found that the rate of early-maturing fruit cracking was lower compared to late-maturing varieties.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…It has been observed that cracking of fruits is not by a single gene, but by several genes, and this trait can be inherited in plants (Vaidyanathan and Harrigan, 2005). The level of cracking differs significantly among several varieties [31][32][33]. In a study on seedless pomegranate varieties, it was found that the rate of early-maturing fruit cracking was lower compared to late-maturing varieties.…”
Section: Genetic Factorsmentioning
confidence: 99%
“…It is essential for cell division, chromosome stability, mitochondria production, cell hydrolysis, and expansion [35][36][37]. Additionally, calcium performs vital biochemical functions and supports many metabolic processes, activating numerous enzyme systems that contribute to the healthy development of plants [38], [39]. It also plays a crucial role in membrane stability and cell integrity.…”
Section: Manganese (Mg Kg -1 )mentioning
confidence: 99%
“…From the study of the genetic map of plants that tolerate higher levels of salinity or drought, we observe an increase in the proportion of the amino acid proline, which is formed in the leaf and then transferred to the rest of the plant (stem and roots), to accumulate starting from glutamate, which is converted to semi aldehyde and then to a proline ring [66,67]. The formation of proline prevents the breakdown of proteins inside the plant and thus prevents their hydrolysis.…”
Section: Relationship Between Proline and Proteinmentioning
confidence: 99%